Brentuximab vedotin in the treatment of cutaneous T‐cell lymphomas: Data from the Spanish Primary Cutaneous Lymphoma Registry. (9th September 2022) - Muniesa, Cristina; Gallardo, Fernando; García‐Doval, Ignacio; Estrach, M. Teresa; Combalia, Andrea; Morillo‐Andújar, Mercedes; De la Cruz‐Vicente, Fátima; Machan, Salma; Moya‐Martínez, Cristina; Rovira, Roger; Sanchez‐Gonzalez, Blanca; Acebo, Elvira; et al.
ABSTRCT: Background: Brentuximab vedotin (BV) has been approved for CD30‐expressing cutaneous T‐cell lymphoma (CTCL) after at least one previous systemic treatment. However, real clinical practice is still limited. Objectives: To evaluate the response and tolerance of BV in a cohort of patients with CTCL. Methods: We analysed CTCL patients treated with BV from the Spanish Primary Cutaneous Lymphoma Registry (RELCP). Results: Sixty‐seven patients were included. There were 26 females and the mean age at diagnosis was 59 years. Forty‐eight were mycosis fungoides (MF), 7 Sézary syndrome (SS) and 12 CD30+ lymphoproliferative disorders (CD30 LPD). Mean follow‐up was 18 months. Thirty patients (45%) showed at least 10% of CD30+ cells among the total lymphocytic infiltrate. The median number of BV infusions received was 7. The overall response rate (ORR) was 67% (63% in MF, 71% in SS and 84% in CD30 LPD). Ten of 14 patients with folliculotropic MF (FMF) achieved complete or partial response (ORR 71%). The median time to response was 2.8 months. During follow‐up, 36 cases (54%) experienced cutaneous relapse or progression. The median progression free survival (PFS) was 10.3 months. The most frequent adverse event was peripheral neuropathy (PN) (57%), in most patients (85%), grades 1 or 2. Conclusions: These results confirm the efficacy and safety of BV in patients with advanced‐stage MF, and CD30 LPD. In addition, patients with FMF and SS also showed a favourable response. Our data suggest that BV retreatment is effective in a proportion of cases.